LATIHAN PEREGANGAN FISIK DI TEMPAT KERJA TERHADAP PENURUNAN KELUHAN LOW BACK PAIN PADA PENENUN SONGKET - Maksuk Maksuk; Desti Syafitri (Poltekkes Kemenkes Kalimantan Timur, 2021)
Low back pain is the most common complaint experienced by songket weavers. The objective study was to analyze the effect of physical stretching exercises at workplace on songket weavers. This study was a quasi-experimental study with a one group pretest and posttest design. The number of samples were 25 weavers (total population). This research was conducted from February to April 2020 at Ketapang Village, Ogan Ilir Regency, South Sumatra. Lower back pain complaint data were collected using Numeric Rating Scale (NRS). Data were analyzed by univariate and bivariate using the Wilcoxon test. The results showed that there was an effect of physical stretching exercises on reducing the pain scale from moderate to mild (p value = 0.0005). Stretching exercises using motion modification William Flexion Exercises have been shown to help reduce back pain. Songket weavers, a complaint of lower back pain, is the most common complaint caused by working hours that exceed working hours every day.